Revascularization procedure in an open apex tooth with external root resorption: A case report - Mahsa Dastpak; Hamid Jafarzadeh; Elham Najafi (Mashhad University of Medical Sciences, 2017)
External inflammatory root resorption (EIR) represents a challenge in endodontic practice. EIR commonly occurs after dental trauma that results in periodontal ligament injury, pulp necrosis and subsequent infection.  Treatment of EIR is based on disinfecting the root canal system through chemomechanical procedures and then filling it with calcium hydroxide or triple antibiotic paste. Dental trauma commonly occurs in young patients whose teeth are not fully formed and have thin dentinal walls and open apices. Revascularization therapy has proven to be suitable for treatment of root canals of teeth with pulp necrosis and open apices. This case report presents successful revascularization treatment of a permanent immature tooth with external root resorption and chronic apical periodontitis. The tooth was treated by the protocol suggested by the American Association of Endodontics (AAE), consisted of disinfecting the root canal system, filling it with blood clot and sealing the root canal with mineral trioxide aggregate followed by bonded resin restoration. The symptoms disappeared, the size of the periapical lesion reduced and the tooth was asymptomatic during the 12 month follow up period.